Bamboos in the Madras State - Andiappan, K.; Wilson, J. (Indian Forester, 1963)
The past working of the bamboo forests of Madras State is briefly discussed, stressing the need for artificial regeneration to restock areas depleted of their bamboo content. The age-old planting methods successfully adopted in rural areas of Thanjavur district are examined; and, suggested for adoption in the forest planting schemes and projects. Despite the higher initial costs of planting (as compared with the usual methods of using one year old nursery stock from seed), the practice of using sturdy 2 to 3 year old nursery stock commends itself in view of the very promising results obtained so far, in the pilot scale plantations raised by the Madras Forest Department.